Postharvest spoilage pathogen associated with turmeric (Curcuma longa L.) product in Southwestern Ethiopia - Jibat, Merga; Alo, Shamil (International Journal of Agricultural Research, Innovation and Technology, 2023)
The primary reason for postharvest deterioration, which is primarily brought on by fungal invasion, is the loss of turmeric products in Southwestern Ethiopia. The study was conducted to determine the main fungi responsible for the postharvest deterioration of turmeric in major turmeric-growing areas of southwestern Ethiopia. In total, 60 samples of dried and stored turmeric were gathered in 2020 and 2021 from different production zones of southwestern Ethiopia. The fungus that causes postharvest turmeric to deteriorate was isolated and identified at the genus level. At the study locations, rhizomes were not cleaned, washed, sorted, or separated from healthy rhizomes. The spoiled turmeric samples contain fungi from four genera: Aspergillus, Penicillium, Fusarium, and Rhizopus. Aspergillus, Penicillium, and Fusarium were isolated from drying and storage samples in all zones. However, Rhizopus was only isolated from samples that had been stored. It was discovered that Aspergillus, Penicillium, and Fusarium were primarily responsible for the observed deterioration. The identified genera's percentage incidence ranged from 15.1% (Fusarium) to 45.2% (Aspergillus). Proper harvesting, postharvest handling procedures, and adopting suitable turmeric harvesting and postharvest handling technology can help decrease turmeric postharvest degradation. Int. J. Agril. Res. Innov. Tech. 13(1): 1-5, June 2023